Overview of 3 year precommercial seafarming of Macrocystis pyrifera along the Chilean coast. (23rd November 2016) - Camus, Carolina; Infante, Javier; Buschmann, Alejandro H.
Abstract: Chile is one of the main producers of seaweeds in the world; however, most of the production comes from harvesting natural beds and only 2.4% from cultures, dominated by the agarophyte Gracilaria chilensis . One of the most exploited resources is the giant kelp Macrocystis pyrifera, which is sold fresh for abalone feed and dry for alginate extraction. Recently, new possible markets are developing for this species, for example human consumption and biofuel/chemical production that could increase the demand and justify the development of a commercial cultivation system. The objective of this work was to present the recent development of the seafarming of M. pyrifera in Chile, focusing on the fundamental determinants of productivity in cultivated systems and the identification of the binding constraints to productivity. Three experimental plots (up to 21 Ha) were designed and deployed in three study areas (Caldera in northern Chile and Quenac and Ancud in southern Chile) to test different environmental conditions. During a period of 3 years, sporophytes produced in an indoor hatchery were deployed monthly, at different densities, and followed until harvest. Environmental parameters and biomass were monitored on a monthly basis. Our findings demonstrate the feasibility of Macrocystis seafarming on a large scale in Chile. Important differences in yield were observed between the study areas associated with either environmental physical or biological factors, such as the presence of herbivores. Our best production cycle reached 124 WMT Ha −1  month −1 in southern Chile, and the worst, less than 20 WMT Ha −1  month −1 in northern Chile. Finally, some direct and indirect constrains were encountered, including seeding season and depth, and the presence of pests and diseases, that are discussed.